APLIKASI MODEL E-MARKETPLACE DALAM E-AGRIBUSINESS - Hilmi Arija Fachriyan; I Putu Eka Wijaya (MEDIAGRO, 2018)
Economic activity is currently entering an era called the era of digital economy. Digital economy involves the process of e-business or e-commerce that utilizes the internet network. The rapid growth of internet users in Indonesia has affected the agribusiness sector to adopt e-commerce called e-agribusiness.In line with the development of the internet, a new understanding of electronic marketing paradigm in e-agribusiness in the form of e-marketplace. Some agribusiness e-marketplace sites have been born in Indonesia such as "agromaret.com", "kecipir.com", "limakilo.id", and "agribisnispedia.com". These five agribusiness e-marketplaces each have their own characteristics, advantages and disadvantages. Basically, the success of an e-marketplace depends heavily on the level of involvement of the participating participants. The lack of e-marketplace reliability is often criticized as one of the key factors that reduce the confidence of sellers or buyers to participate. The process of maturing the e-marketplace is needed to influence the user's perception of the quality of the technical service, the quality of the content service and the quality of customer service. Therefore, there is pressure on the provider side to improve the quality of its services and offer something unique above industry standards to achieve a competitive advantage over other agribusiness e-marketplaces. Keywords:e-commerce, e-agribusiness, e-marketplace.